Getting a good view: in vitro imaging of platelets under flow. (3rd July 2020) - Oshinowo, Oluwamayokun; Lambert, Tamara; Sakurai, Yumiko; Copeland, Renee; Hansen, Caroline E.; Lam, Wilbur A.; Myers, David R.
Abstract: As the anucleate cells responsible for hemostasis and thrombosis, platelets are exposed to a myriad of biophysical and biochemical stimuli within vasculature and heterogeneous blood clots. Highly controlled, reductionist in vitro imaging studies have been instrumental in providing a detailed and quantitative understanding of platelet biology and behavior, and have helped elucidate some surprising functions of platelets. In this review, we highlight the tools and approaches that enable visualization of platelets in conjunction with precise control over the local biofluidic and biochemical microenvironment. We also discuss next generation tools that add further control over microenvironment cell stiffness or enable visualization of the interactions between platelets and endothelial cells. Throughout the review, we include pragmatic knowledge on imaging systems, experimental conditions, and approaches that have proved to be useful to our in vitro imaging studies of platelets under flow.